A Co-Pilot as Artificial Intelligence and Local Culture Integration in Writing Instruction: A Model to Improve Students’ Engagement in Polytechnic - M Bambang Purwanto; Dahnial; Fitri Nurdianingsih (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates integrating local culture into writing instruction to improve students’ engagement in a polytechnic context. The research employed a Classroom Action Research design in two cycles, involving 30 fourth-semester students in a tourism study program. Local culture-based writing activities were implemented through topics such as describing local tourist attractions and reporting cultural events. Data were collected using observation checklists, students’ writing tasks, and field notes, and analyzed through data reduction, data display, and conclusion drawing. The findings revealed that integrating local culture increased students’ behavioral, emotional, and cognitive engagement. Students became more active in discussions, showed greater enthusiasm, and developed ideas more easily. In addition, students’ writing performance improved across organization, vocabulary, grammar, and content. The use of familiar cultural contexts helped students produce more relevant and meaningful texts. The study concludes that integrating local culture into writing instruction is an effective strategy to enhance engagement and improve writing performance in vocational education.